EFFECT OF DEBT TO EQUITY RATIO, CURRENT RATIO AND DEBT TO ASSET RATIO ON RETURN ON ASSET AT KUD TANI BAHAGIA, INDRAGIRI HULU REGENCY - Angga Hapsila; Ivalaina Astarina; Agus Supriyadi; Yudha Remofa; Puspa Dewi (JURNAL MANAJEMEN DAN BISNIS, 2021)
This research was conducted forknow the effectDebt to Equity Ratio, Current Ratio and Debt to  Assets Ratio to Return on Assets at KUD Tani Bahagia, Indragiri Hulu Regency. This study uses  secondary data by looking at the financial statements at KUD Tani Bahagia. The researcher processed the data using multiple linear regression which processed it using SPSS (statistical package for social science) version 21 to get the output to conclude the results of this study. From research results that is Debt to Equity Ratio, Current Ratio and Debt to Assets Ratio partially effect toReturn on Assets at KUD Tani Bahagia.